High weather resistance adhesive and preparation method thereof
By using resin mixtures and reactive diluents in adhesives, a stable crosslinking structure and modified silica is formed, which solves the problem of failure of traditional adhesives in high temperature, high humidity or low temperature environments, and achieves a high weather resistance adhesive, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411920041.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
Traditional adhesives are prone to failure in high temperature and high humidity or low temperature environments, resulting in cracking of the adhesive layer or leakage of moisture, oxygen, etc., which is difficult to meet the weather resistance requirements of semiconductors, automobiles and other application scenarios.
The weather resistance of the adhesive is improved by forming a stable three-dimensional mesh crosslinking structure and the use of modified silica using a combination of resin mixtures (including bisphenol A epoxy resin, bisphenol F epoxy resin and polyurethane modified epoxy resin) with active diluents, inorganic fillers, initiators and additives.
The adhesive has been able to work stably for a long time between -20℃ and 60℃, and its adhesion, flexibility and thermal oxidation stability are improved. It is suitable for semiconductors, photovoltaics, automobiles and other scenarios.
Smart Images

Figure CN119752376A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives, and in particular to a highly weather-resistant adhesive and a preparation method thereof. Background Art
[0002] Adhesives have a wide range of applications in life and play an important role in production and life. Traditional adhesives play a bonding role and can maintain good bonding effects at room temperature and pressure. However, in some special fields or conditions that require high weather resistance, the bonding effect of ordinary adhesives will be greatly reduced. For example, traditional adhesives will easily fail in high temperature and high humidity environments; without targeted reinforcement, general adhesives do not perform well at low temperatures, and the colloid itself becomes brittle due to low temperatures, making it more prone to breakage and other undesirable phenomena. For example, when bonding on metal surfaces, unlike glass surfaces that have a large number of hydrogen bonds and can achieve better bonding effects, the metal surface is smoother and has no hydrogen bonds, resulting in significantly reduced adhesion effects. For application scenarios with high temperature and high humidity or excessive temperature changes in application scenarios, ordinary adhesives are prone to low-temperature cold brittleness or rapid aging in high temperature and high humidity environments, and are prone to bonding layer breakage or leakage of water and oxygen. Especially in application scenarios such as semiconductors and automobiles, such drastic changes in conditions are very common.
[0003] Therefore, there is an urgent need for an adhesive with high weather resistance that can be used in special scenarios. Summary of the invention
[0004] The main purpose of the present invention is to provide a highly weather-resistant adhesive and a preparation method thereof, so as to solve the problem of poor weather resistance of conventional adhesives in the prior art.
[0005] In order to achieve the above-mentioned object, the present invention provides a high weather-resistant adhesive, wherein the raw material components include, by weight: 20 to 80 parts of a resin mixture, 5 to 30 parts of an active diluent, 20 to 60 parts of an inorganic filler, 0.1 to 10 parts of an initiator, and 0.1 to 5 parts of an auxiliary agent; the resin mixture includes bisphenol A epoxy resin, bisphenol F epoxy resin, and polyurethane-modified epoxy resin.
[0006] Optionally, the mass ratio of the bisphenol A epoxy resin, the bisphenol F epoxy resin and the polyurethane modified epoxy resin is: (10-30): (10-30): (1-20).
[0007] Optionally,
[0008] The epoxy equivalent of the bisphenol A epoxy resin is 150-250 g / eq, the viscosity of the bisphenol A epoxy resin is 10000-25000 cps, and the bisphenol A epoxy resin is liquid at 25°C.
[0009] The epoxy equivalent of the bisphenol F epoxy resin is 150-250 g / eq, the viscosity of the bisphenol F epoxy resin is 5000-20000 cps, and the bisphenol F epoxy resin is liquid at 25°C.
[0010] The epoxy equivalent of the polyurethane modified epoxy resin is 160-260 g / eq, the viscosity of the polyurethane modified epoxy resin is 35000-200000 cps, and the polyurethane modified epoxy resin is liquid at 25°C.
[0011] Optionally, the reactive diluent is epoxy glycidyl ether, and the epoxy glycidyl ether is one or more combinations of benzyl glycidyl ether, allyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, C12-14 glycidyl ether, bisphenol A epoxy glycidyl ether and bisphenol F epoxy glycidyl ether.
[0012] Optionally, the initiator comprises a mixture of a photoinitiator and a thermal initiator.
[0013] Optionally, in the initiator mixture, the mass ratio of the photoinitiator to the thermal initiator is (0.1-5): (0.1-5).
[0014] Optionally, the auxiliary agent includes an adhesion promoter, a defoamer, a leveling agent and a dispersant.
[0015] Optionally, the silica is silica modified by a modifier; the modifier includes one of a silane coupling agent, polyacrylamine, POSS, titanate, fatty acid, organic acid and inorganic acid.
[0016] The present invention also provides a method for preparing a highly weather-resistant adhesive, which is applied to the highly weather-resistant adhesive of the present invention, and the preparation method comprises:
[0017] Step 1: Weigh the measured initiator and active diluent, mix and stir the two, and after the initiator is completely dissolved, obtain a first mixture.
[0018] Step 2: Weigh the measured bisphenol A epoxy resin, bisphenol F epoxy resin, polyurethane modified epoxy resin and inorganic filler, add them into a double planetary mixer, and premix them at a temperature of 50 to 60° C. to obtain a second mixture;
[0019] Step 3, adding the first mixture and the auxiliary agent into the second mixture, stirring, to obtain a third mixture;
[0020] Step 4: Place the third mixture in a three-roll mill for grinding and dispersion, and take samples to detect the particle size during the grinding and dispersion process. When the particle size is less than 15 μm, stop grinding to obtain a fourth mixture, and vacuum degas the fourth mixture and fill it into a syringe to obtain the highly weather-resistant adhesive.
[0021] The invention discloses a highly weather-resistant adhesive and a preparation method thereof. The raw material components include, by weight, 20 to 80 parts of a resin mixture, 5 to 30 parts of an active diluent, 20 to 60 parts of silicon dioxide, 0.1 to 10 parts of an initiator, and 0.1 to 5 parts of an auxiliary agent. The resin mixture includes bisphenol A epoxy resin, bisphenol F epoxy resin, and polyurethane-modified epoxy resin. The polyurethane-modified epoxy resin can improve the flexibility of the adhesive. The polyurethane-modified epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin, and inorganic filler form a stable three-dimensional network cross-linked structure, which has a high Tg and high weather resistance. It can work stably for a long time in low and high temperature environments and has a wider application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0023] Figure 1 The present invention is a flow chart of a method for preparing a highly weather-resistant adhesive that can be selected according to an embodiment of the present invention. DETAILED DESCRIPTION
[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0025] A high weather resistance adhesive comprises, by weight, 20 to 80 parts of a resin mixture, 5 to 30 parts of an active diluent, 20 to 60 parts of an inorganic filler, 0.1 to 10 parts of an initiator, and 0.1 to 5 parts of an auxiliary agent.
[0026] The resin mixture includes bisphenol A epoxy resin, bisphenol F epoxy resin and polyurethane modified epoxy resin.
[0027] Specifically, resin mixtures are all curable resins. The bisphenol A epoxy resin and bisphenol F epoxy resin used in this application are all high Tg resins, wherein, in the structure of bisphenol A epoxy resin, there are hydroxyl (—CH—OH), ether group (—O—) and extremely active epoxy groups, and hydroxyl and ether groups have a high degree of polarity, so that the epoxy molecules and adjacent interfaces produce a strong intermolecular force, and the epoxy group reacts with the free bond on the surface of the medium to form a chemical bond, which has a very high adhesive force. Bisphenol F epoxy resin has a small viscosity and good fluidity. The high strength of bisphenol A epoxy resin and the low viscosity of bisphenol F epoxy resin are combined to help improve the strength and elasticity of the prepared adhesive. Polyurethane-modified epoxy resin is a resin obtained by modifying epoxy resin with polyurethane, combining the elasticity and weather resistance of polyurethane with the high strength and chemical corrosion resistance of epoxy resin, and has excellent flexibility, impact resistance and weather resistance. Introducing polyurethane-modified epoxy resin into the adhesive can improve the flexibility of the adhesive and reduce the occurrence of cold brittleness under low temperature conditions. In addition, bisphenol A epoxy resin, bisphenol F epoxy resin and polyurethane-modified epoxy resin undergo cross-linking polymerization reaction under the action of the initiator, and together with the inorganic filler, form an island-like structure, which plays a role in blocking water and oxygen from the outside and resisting corrosion from the inside, thereby improving the Tg of the overall adhesive, so that the elastic state of the colloid will not change due to excessive temperature during and after the curing process of the adhesive, thereby affecting the performance of the colloid, and it has high thermal oxidation stability and chemical corrosion resistance. The adhesive in this application has a high Tg temperature and can work stably for a long time between -20°C and 60°C. At the same time, it has excellent adhesion and flexibility, and can be widely used in many scenarios such as semiconductors, photovoltaics, and automobiles.
[0028] In addition, silica as a filler makes the adhesive have the characteristics of fast heat dissipation, low CTE and low curing shrinkage, and can improve the insulation ability of the adhesive. The active diluent reduces the overall viscosity of the adhesive when it is not cured, which is convenient for processing and use. After curing, it reacts and connects with the mixed resin to form a three-dimensional cross-linked network structure. The auxiliary agent is a commonly used additive in the preparation of adhesives. CTE is the coefficient of thermal expansion.
[0029] In a possible implementation manner, the mass ratio of bisphenol A epoxy resin, bisphenol F epoxy resin and polyurethane modified epoxy resin is (10-30): (10-30): (1-20).
[0030] Specifically, the applicant found that under this ratio, the prepared adhesive has better mechanical properties at low temperatures and is not prone to cold brittleness leading to bonding failure.
[0031] In one possible implementation,
[0032] The epoxy equivalent of bisphenol A epoxy resin is 150-250 g / eq, the viscosity of bisphenol A epoxy resin is 10000-25000 cps, and the bisphenol A epoxy resin is liquid at 25°C.
[0033] The epoxy equivalent of the bisphenol F epoxy resin is 150-250 g / eq, the viscosity of the bisphenol F epoxy resin is 5000-20000 cps, and the bisphenol F epoxy resin is liquid at 25°C.
[0034] The epoxy equivalent of the polyurethane modified epoxy resin is 160-260 g / eq, the viscosity of the polyurethane modified epoxy resin is 35000-200000 cps, and the polyurethane modified epoxy resin is liquid at 25°C.
[0035] Specifically, high Tg bisphenol A epoxy resin, bisphenol F epoxy resin and polyurethane modified epoxy resin are all liquid at 25°C, which is easier to handle during mixing and processing, and is conducive to uniform mixing and good infiltration. The viscosity of bisphenol A epoxy resin is greater than that of bisphenol F epoxy resin. Bisphenol A epoxy resin is mainly used to improve the strength of adhesives, while bisphenol F epoxy resin is mainly used to improve the fluidity of adhesives.
[0036] Among them, bisphenol A epoxy resin can be selected from 828, 828EL, 1510 of Hansen Company, or 840, 840-S, 850, 850-S, 850-CRP, 860 of DIC Company, or KE-8120 of Cologne Company, YLE-1300A, YLE-1900A, YLE-475, NR-828K-1 of GLK Company. Bisphenol F epoxy resin can be selected from 830, 830-S, EXA-830LVP, 835, EXA-835LV of DIC Company, KF-8110 of Cologne Company, YLE-1300F, YLF-1700F of GLK Company. Polyurethane modified epoxy resin can be selected from DER791, 852, 858 of Dow Chemical, NPER-133L of Nanya, EU-1000 of Dow Chemical Company.
[0037] In one possible embodiment, the active diluent is epoxy glycidyl ether, and the epoxy glycidyl ether is one or more combinations of benzyl glycidyl ether, allyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, C12-14 glycidyl ether, bisphenol A epoxy glycidyl ether and bisphenol F epoxy glycidyl ether.
[0038] Specifically, using benzyl glycidyl ether, allyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, C12-14 glycidyl ether, bisphenol A epoxy glycidyl ether and bisphenol F epoxy glycidyl ether as active diluents of epoxy resin can improve processing performance and optimize the performance of adhesive. Preferably, epoxy glycidyl ether is one or a mixture of bisphenol A epoxy glycidyl ether or bisphenol F epoxy glycidyl ether. Bisphenol A epoxy glycidyl ether or bisphenol F epoxy glycidyl ether has a fast initiation speed, and can be combined with epoxy resin to further increase the crosslinking density, form a tighter three-dimensional network structure, and further improve the stability and weather resistance of the adhesive.
[0039] In one possible embodiment, the initiator includes a mixture of a photoinitiator and a thermal initiator.
[0040] Specifically, photoinitiators and thermal initiators can produce synergistic effects in the reaction. Among them, the photoinitiator absorbs light energy under illumination conditions and converts it into chemical energy, thereby initiating a chemical reaction, while the thermal initiator reacts the active hydrogen with the epoxy group after reaching a certain temperature, and also initiates a chemical reaction. The combination of the two enables the reaction to be carried out under wider temperature and illumination conditions, thereby improving the reaction efficiency. In practical downstream applications, ultraviolet light is first used for curing, and after the adhesive is preliminarily cured, it is heated for deep curing. While the synergistic effect of light and heat can ensure a good curing effect, it is also more convenient for practical application in terms of process. In the present application, the photoinitiator is one or more of OXE-01, PAG-002, Omnicat 550, and Omnicat 440. The thermal initiator is an epoxy thermal initiator, such as a hydrazide thermal initiator.
[0041] In a possible implementation manner, in the initiator mixture, the mass ratio of the photoinitiator to the thermal initiator is (0.1-5): (0.1-5).
[0042] Specifically, a suitable ratio of the initiator helps the colloid to achieve a good curing effect under light and heating conditions, so that the cured colloid has good mechanical properties and high weather resistance.
[0043] In a possible implementation, the auxiliary agent includes an adhesion promoter, a defoaming agent, a leveling agent and a dispersant.
[0044] Specifically, the adhesion promoter is evenly dispersed in the resin system, promoting the compatibility of the filler and the resin, and improving the dispersion uniformity of the system. At the same time, as an additive in the adhesive, it can also promote the wetting of the adhesive on the surface of the substrate and improve the wetting of the adhesive on the surface of inorganic metal / glass, which is beneficial to the improvement of the adhesion of the adhesive.
[0045] During the preparation of adhesives, due to changes in temperature, pressure, stirring and other factors, a large number of large bubbles and micron-sized bubbles will exist in the adhesive system. The defoamer added to the system can stably exist in the adhesive system, continue to play a foam-inhibiting role, prevent the generation of new bubbles, and ensure the stability and quality of the adhesive. The leveling agent can improve the fluidity of the adhesive, so that the adhesive can be more evenly covered on the surface of the substrate during coating, and work synergistically with the adhesion promoter to promote the adhesion between the adhesive and the substrate surface. The dispersant can improve the dispersibility of the filler in the adhesive, avoid filler agglomeration and precipitation, and make the adhesive more uniform and stable.
[0046] The defoamer is one or more of Defom 2700, 5300, 5500, 6500, 6800, and DAPRO AP1622, and the adhesion promoter is one or more of KBM-903, KBM-403, KBM-503, KBM-603, and KBM-602. The leveling agent is one or more of Levelol 839, Levaslip 810, and Levaslip 435. The dispersant includes one or more of BYK-9076, DISPERBYK-2152, DISPERBYK-108, DISPERBYK-109, and DISPERBYK-145.
[0047] In a possible implementation, the inorganic filler is silica modified by a modifier; the modifier includes one of a silane coupling agent, polyacrylamine, POSS, titanate, fatty acid, organic acid and inorganic acid.
[0048] Specifically, the particle size of the silicon dioxide is 1 to 10 μm. The silicon dioxide modified by the modifier has better compatibility with the resin system in the adhesive.
[0049] The present invention also provides a method for preparing a highly weather-resistant adhesive, which is used in the present application. The preparation method comprises:
[0050] Step 1, weighing the measured initiator and active diluent, mixing and stirring the two, and obtaining a first mixture after the initiator is completely dissolved;
[0051] Step 2: Weigh the measured bisphenol A epoxy resin, bisphenol F epoxy resin, polyurethane modified epoxy resin and inorganic filler, add them into a double planetary mixer, and premix them at a temperature of 50 to 60° C. to obtain a second mixture;
[0052] Step 3, adding the first mixture and the auxiliary agent into the second mixture, stirring, to obtain a third mixture;
[0053] Step 4: Grind and disperse the third mixture in a three-roll mill, and take samples to detect the particle size during the grinding and dispersing process. When the particle size is less than 15 μm, stop grinding to obtain a fourth mixture; vacuum degas the fourth mixture and fill it into a syringe to obtain a highly weather-resistant adhesive.
[0054] Specifically, since the initiator is a powder, it is easy to have uneven dispersion problems when directly mixed with other components. The reactive diluent has a lower viscosity and can well wet and disperse the powder initiator, thereby improving the uniformity of mixing. Therefore, in the present application, the metered initiator and the low-viscosity reactive diluent are first mixed to make the initiator uniformly dissolved in the reactive diluent to obtain a first mixture. Then the metered bisphenol A epoxy resin, bisphenol F epoxy resin, polyurethane-modified epoxy resin and inorganic filler are premixed in a double planetary mixer, and the temperature is controlled to be 50-60°C to obtain a second mixture. The first mixture and the auxiliary agent are added to the second mixture, stirred and mixed to obtain a third mixture, and the third mixture at this time is an adhesive containing inorganic filler particles. The third mixture is ground and dispersed using a three-roller machine, and samples are taken multiple times during the grinding and dispersion process, and the scraper fineness meter is used for detection. When the test results show that the size of the largest particle or agglomerate is less than 15μm, it can be considered that the adhesive has achieved good dispersion uniformity at this time, and the grinding is stopped. Evenly dispersed adhesives can reduce local stress concentration and microcrack formation caused by particle agglomeration, thereby improving the weather resistance and service life of the adhesive.
[0055] The present invention is further illustrated by the following examples.
[0056] Example 1
[0057] Bisphenol A epoxy resin 30%, bisphenol F epoxy resin 15%, polyurethane modified epoxy resin 10%, reactive diluent 10%, surface modified silica 30%, photoinitiator 2.5%, thermal initiator 1%, adhesion promoter 0.5%, defoamer 0.3%, leveling agent 0.2%, dispersant 0.5%.
[0058] Step 1: Mix and stir 2.5% of a photoinitiator, 1% of a thermal initiator and 10% of a reactive diluent, and obtain a first mixture after the initiator is completely dissolved;
[0059] Step 2: Add 30% of bisphenol A epoxy resin, 15% of bisphenol F epoxy resin, 10% of polyurethane modified epoxy resin and 30% of surface modified silica into a double planetary mixer, and premix at a temperature of 50 to 60° C. to obtain a second mixture;
[0060] Step 3, adding the first mixture and the auxiliary agent into the second mixture, stirring, to obtain a third mixture;
[0061] Step 4: Grind and disperse the third mixture in a three-roll mill, take samples several times during the grinding and dispersion process, and test it with a scraper fineness meter. When the test results show that the size of the largest particles or agglomerates is less than 15 μm, stop grinding to obtain a fourth mixture; vacuum degas the fourth mixture and fill it into a syringe to obtain adhesive 1, and the syringe can be degassed for a second time before testing.
[0062] The physical properties of the prepared adhesive 1 are as follows:
[0063] In the uncured state: viscosity = 154728 mPa·s;
[0064] In the cured state: hardness = 80D (Shore), water absorption = 0.5%, adhesion = 10.89Mpa, elongation at break = 4.69%, tensile strength = 31.28Mpa, Young's modulus = 1.13Gpa, cure rate = 99.1%, Tg = 147℃, CTE = 121ppm / ℃. The number of thermal shock cycles (-40 to 80℃, 30mins at each temperature, switching time less than 15s) is 586 times.
[0065] Example 2
[0066] Bisphenol A epoxy resin 33.33%, bisphenol F epoxy resin 16.66%, polyurethane modified epoxy resin 5%, reactive diluent 10%, surface modified silica 30%, photoinitiator 2.5%, thermal initiator 1%, adhesion promoter 0.5%, defoamer 0.3%, leveling agent 0.2%, dispersant 0.5%.
[0067] Step 1: Mix and stir 2.5% of a photoinitiator, 1% of a thermal initiator and 10% of a reactive diluent, and obtain a first mixture after the initiator is completely dissolved;
[0068] Step 2: adding 33.33% of bisphenol A epoxy resin, 16.66% of bisphenol F epoxy resin, 5% of polyurethane modified epoxy resin and 30% of surface modified silica into a double planetary mixer, and premixing at a temperature of 50-60° C. to obtain a second mixture;
[0069] Step 3, adding the first mixture and the auxiliary agent into the second mixture, stirring, to obtain a third mixture;
[0070] Step 4: Grind and disperse the third mixture in a three-roll mill, take samples several times during the grinding and dispersion process, and test it with a scraper fineness meter. When the test results show that the size of the largest particles or agglomerates is less than 15 μm, stop grinding to obtain a fourth mixture; vacuum degas the fourth mixture and fill it into a syringe to obtain adhesive 2, and the syringe can be degassed for a second time before testing.
[0071] The physical properties of the prepared adhesive 2 are as follows:
[0072] In the uncured state: viscosity = 93267mPa·s;
[0073] In the cured state: hardness = 65D (Shore), water absorption = 4.2%, adhesion = 4.88Mpa, elongation at break = 2.79%, tensile strength = 18.19Mpa, Young's modulus = 645.69MPa, cure rate = 99.0%, Tg = 114°C, CTE = 335ppm / °C. The number of thermal shock cycles (-40 to 80°C, 30mins at each temperature, switching time less than 15s) is 341 times.
[0074] Example 3: 36% bisphenol A epoxy resin, 18% bisphenol F epoxy resin, 1% polyurethane modified epoxy resin, 10% reactive diluent, 30% surface modified silica, 2.5% photoinitiator, 1% thermal initiator, 0.5% adhesion promoter, 0.3% defoamer, 0.2% leveling agent, and 0.5% dispersant.
[0075] Step 1: Mix and stir 2.5% of a photoinitiator, 1% of a thermal initiator and 10% of a reactive diluent, and obtain a first mixture after the initiator is completely dissolved;
[0076] Step 2: adding 36% of bisphenol A epoxy resin, 18% of bisphenol F epoxy resin, 1% of polyurethane modified epoxy resin and 30% of surface modified silica into a double planetary mixer, and premixing at a temperature of 50 to 60° C. to obtain a second mixture;
[0077] Step 3, adding the first mixture and the auxiliary agent into the second mixture, stirring, to obtain a third mixture;
[0078] Step 4: Grind and disperse the third mixture in a three-roll mill, take samples several times during the grinding and dispersion process, and test it with a scraper fineness meter. When the test results show that the size of the largest particles or agglomerates is less than 15 μm, stop grinding to obtain a fourth mixture; vacuum degas the fourth mixture and fill it into a syringe to obtain adhesive 3, and the syringe can be degassed for a second time before testing.
[0079] The physical properties of the prepared adhesive 3 are as follows:
[0080] In the uncured state: viscosity 34251mPa·s;
[0081] In the cured state: hardness 45D (Shore), water absorption 8.3%, adhesion 0.84Mpa, elongation at break 0.88%, tensile strength 7.63Mpa, Young's modulus 112.59Mpa, cure rate 98.9%, Tg = 86°C, CTE = 534ppm / °C. The number of thermal shock cycles (-40 to 80°C, 30mins at each temperature, switching time less than 15s) is 68 times.
[0082] Through the measured performance of the examples, it can be seen that the prepared adhesives are all weather-resistant. The addition of polyurethane-modified epoxy resin can not only improve the mechanical properties of the adhesive material, but also significantly improve the adhesion, toughness, Tg, etc. of the colloid, especially the performance improvement under hot and cold shock is more obvious, and when the addition amount of polyurethane-modified epoxy resin is 1%, the hot and cold shock cycle can reach 68 times, and when the addition amount increases to 10%, it can achieve 586 cycles, which shows that the improvement effect on weather resistance is obvious.
[0083] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A highly weather-resistant adhesive, characterized in that: The raw material components include, by weight: 20 to 80 parts of resin mixture, 5 to 30 parts of active diluent, 20 to 60 parts of inorganic filler, 0.1 to 10 parts of initiator, and 0.1 to 5 parts of auxiliary agent; The resin mixture comprises bisphenol A epoxy resin, bisphenol F epoxy resin and polyurethane modified epoxy resin.
2. The highly weather-resistant adhesive according to claim 1, characterized in that: In the resin mixture, the mass ratio of the bisphenol A epoxy resin, the bisphenol F epoxy resin and the polyurethane modified epoxy resin is: (10-30): (10-30): (1-20).
3. The highly weather-resistant adhesive according to claim 2, characterized in that: The epoxy equivalent of the bisphenol A epoxy resin is 150-250 g / eq, the viscosity of the bisphenol A epoxy resin is 10000-25000 cps, and the bisphenol A epoxy resin is liquid at 25°C. The epoxy equivalent of the bisphenol F epoxy resin is 150-250 g / eq, the viscosity of the bisphenol F epoxy resin is 5000-20000 cps, and the bisphenol F epoxy resin is liquid at 25°C. The epoxy equivalent of the polyurethane modified epoxy resin is 160-260 g / eq, the viscosity of the polyurethane modified epoxy resin is 35000-200000 cps, and the polyurethane modified epoxy resin is liquid at 25°C.
4. The highly weather-resistant adhesive according to claim 1, characterized in that: The active diluent is epoxy glycidyl ether, and the epoxy glycidyl ether is one or more combinations of benzyl glycidyl ether, allyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, C12-14 glycidyl ether, bisphenol A epoxy glycidyl ether and bisphenol F epoxy glycidyl ether.
5. The highly weather-resistant adhesive according to claim 1, characterized in that: The initiator includes a mixture of a photoinitiator and a thermal initiator.
6. The highly weather-resistant adhesive according to claim 5, characterized in that: In the initiator mixture, the mass ratio of the photoinitiator to the thermal initiator is (0.1-5): (0.1-5).
7. The highly weather-resistant adhesive according to claim 1, characterized in that: The auxiliary agents include adhesion promoters, defoamers, leveling agents and dispersants.
8. The highly weather-resistant adhesive according to claim 1, characterized in that: The inorganic filler is silicon dioxide modified by a modifier; the modifier includes one of a silane coupling agent, polyacrylamine, POSS, titanate, fatty acid, organic acid and inorganic acid.
9. A method for preparing a highly weather-resistant adhesive, characterized in that: The highly weather-resistant adhesive according to any one of claims 1 to 8, wherein the preparation method comprises: Step 1, weighing the measured initiator and active diluent, mixing and stirring the two, and obtaining a first mixture after the initiator is completely dissolved; Step 2: Weigh the measured bisphenol A epoxy resin, bisphenol F epoxy resin, polyurethane modified epoxy resin and inorganic filler, add them into a double planetary mixer, and premix them at a temperature of 50 to 60° C. to obtain a second mixture; Step 3, adding the first mixture and the auxiliary agent into the second mixture, stirring, to obtain a third mixture; Step 4: Grind and disperse the third mixture in a three-roll mill, and take samples to detect the particle size during the grinding and dispersing process. When the particle size is less than 15 μm, stop grinding to obtain a fourth mixture; vacuum degas the fourth mixture and fill it into a syringe to obtain the highly weather-resistant adhesive.
Citation Information
Cited By
Composite material coating capable of being used for attaching TPU (thermoplastic polyurethane) to PC-ABS (polycarbonate-acrylonitrile-butadiene-styrene)
CN120966339A